A conceptual framework for ecological economics based on systemic principles of life. Issue 6 (12th June 2017) - Capra, Fritjof; Jakobsen, Ove Daniel
Abstract : Purpose: The purpose of this paper is to refer to ecological economics using two meanings of the term "ecological". In the strict scientific sense, ecological economics refers to an economic system that is consistent with and honors the basic principles of ecology, which, ultimately, are identical with what the authors call the systemic principles of life. In a broader sense ecological economics refers to economic theory and practice that see the economy as operating within, rather than dominating, the spheres of nature, society, and culture. Design/methodology/approach: The authors distill four fundamental principles for ecological economics based on systems theory of life and philosophy of organism. The four principles are; nested systems, self-generating networks, open systems, and cognitive interactions. The authors discuss how these principles can be applied to design an ecological economic system that is life-enhancing on individual, social and ecological levels. Findings: The authors argue that ecological economics should give priority to activities that maximize well-being of human and non-human beings, as well as entire ecosystems, and that its central purpose should be to serve the life processes in social and ecological systems. Originality/value: In this paper, the authors connect ecological economics to systems theory and come up with principles relevant for developing economic theory and practice within, rather than dominating, the spheres of nature, society, and culture.